Soluble Transferrin Receptor (sTfR) Identifies Iron Deficiency Anemia (IDA) in Pulmonary Tuberculosis Patients - Tri Ratnaningsih; Novi W Sukirto; Arum Tri Wahyuningsih (Acta Medica Indonesiana, 2020)
Background: iron deficiency in pulmonary tuberculosis (TB) patients may weaken their immune system, causing difficulty in overcoming the infection. Accurate diagnosis of iron deficiency anemia (IDA) in pulmonary TB patients is essential. In order to prove the iron deficient state, diagnosis should focus on inflammatory factors, which could highly affect the outcome of iron status, such as measurement of serum ferritin (SF). Soluble Transferrin Receptor (sTfR) is the best parameter to diagnose iron deficiency in the inflammatory condition. This study aimed to understand the role of sTfR to identify IDA in TB patients. Methods: cross-sectional study were applied to 3 study groups: anemic pulmonary TB (68 subjects), IDA (7 subjects), and non-anemic pulmonary TB (15 subjects). The test averages and correlations between sTfR, SF, and other hematological parameters were measured and analyzed. Results: significant differences of sTfR were found in the anemic TB group compared to the IDA group and also between the IDA and non-anemic TB groups (p<0.0001). However, there was no significant difference (p>0.05) between TB anemic and non-anemic groups. We also found no significant difference between the TB anemic sub-group with normal levels of sTfR compared with the non-anemic group. There was no significant difference of sTfR levels between sub-group of increasing sTfR and group IDA (p>0.05). However, there was strong correlation between sTfR and SF in the IDA group (r=-0.89; p=0.007). Conclusion: the findings suggest verifying the sTfR amount in anemic patients with pulmonary TB suffering from inflammation, so that the iron deficiency could be more accurately identified and properly treated.